A community based comparative study on gender perceptions among married (reproductive age) women of rural and urban areas of district Gautam Buddha Nagar - Pawaiya, Amit Singh; Juneja, Khushboo; Jha, Ajay Kumar; Shree, Tuhina; Makhija, Ankita; Jain, Ieshitva; Nagesh, S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The preference for a son over female offspring continues to be a prevailing norm within the ancient Indian family. Sons are expected to work within the fields, give bigger financial gain and look after parents. Additionally, in Indian patriarchal society, sons are a unit responsible for the preservation of the family name. The preference for a son and female feticide continues to be a prevailing norm in ancient Indian families (urban and rural) leading to declining sex ratio to an alarming level. With this background the following study was conducted in Gautam Buddha Nagar with the objective of finding out gender bias in rural and urban area. Methods: A study was carried out in rural and urban field practice area of the Department of Community Medicine, district Gautam Buddha Nagar of Uttar Pradesh. The study was conducted among 270 married women of reproductive age group. The women were interviewed using a semi structure questionnaire. Results: More than half of the respondents in the rural areas (57.7%) preferred son while in the urban areas, 43% of women preferred a son. The most important reason for preferring a son in the rural area was a support to the parents. While in urban area son was preferred because of the continuation of a family line. Conclusions: Preference for son was found to be high. Further amendments in the existing laws and quality education may help in breaking gender stereotypes and minimizing gender bias.